SOLUBILITY OF CHLORARGYRITE (AGCL) IN WATER VAPOR AT ELEVATED TEMPERATURES AND PRESSURES - Migdisov A.A.; Williams-Jones A.E.; Suleimenov O.M. (My University, 1999)
The solubility of chlorargyrite (AgCl) in undersaturated water vapor was investigated at temperatures of 300 to 360oC and pressures up to 180 bars. It was shown that the presence of water vapor increases the concentration of AgCl in the gas (vapor) phase by between 1.5 and 2 orders of magnitude. This phenomenon is attributed to the formation of hydrated gaseous particles. Silver chloride dissolved in water vapor without changing its stoichiometry (congruent dissolution, Ag:Cl = 1:1). On the basis of the experimental data obtained in this study, the process of chlorargyrite dissolution, and the formation of hydrated gaseous particles in water vapor can be described by the reaction: AgClcryst.+3·H2Ogas=AgCl·(H2O)3gas Considering that Ag is coordinated by three molecules of water and one molecule of chlorine in the AgCl · (H2O)3gas particle, it was assumed that the silver atom is in fourfold coordination. The properties of the AgCl · (H2O)3 particle were refined using ab initio molecular orbital calculations, and the stable geometry of the particle was deduced to have C3 symmetry.The temperature dependence of the equilibrium constant for the reaction controlling the formation of AgCl · (H2O)3gas is described by the equation: logK(P=1bar)=(22.578±5.505)−(0.0255±0.0045)·TK−(11987.6±658.5)/TK Preliminary calculations suggest that water vapor can transport significant quantities of silver, and that such transport may play an important role in mobilizing silver in natural hydrothermal systems.